Studi Komparatif Antara Jual Beli ‘Īnah Dan Murābaḥah Li Al-Āmir Bi Al-Shirā’ Dalam Perspektif Hukum Ekonomi Syariah - Kholistyah, Uswatun; Fuadi, Rial (Jurnal Hukum Ekonomi Syariah, 2025)
Murābaḥah is one of the key instruments in Islamic financing, yet it is often perceived as indistinguishable from conventional credit systems. Issues such as the use of wakālah contracts and the unclear ownership status of goods by the bank have led to assumptions that this practice resembles ‘īnah transactions, which are widely criticized as a disguised form of riba (usury). This study investigates the legal status and substantive differences between the contracts of ‘īnah sale and murābaḥah li al-āmir bi al-shirā’ from the perspective of Islamic economic law. Using a qualitative method with a normative-conceptual approach, the research is based on classical and contemporary literature. The findings reveal that although the two contracts share structural similarities, they differ significantly in terms of concept, legal implications, and underlying rationale (‘illah). Murābaḥah li al-āmir bi al-shirā’ is considered more consistent with Islamic legal principles, emphasizing justice, transparency, and the avoidance of riba. These findings contribute to the development of Islamic financing models that better align with the fundamental objectives of Sharia.  Keywords: Bay‘ al-‘Īnah, Murābaḥah li al-Āmir bi al-Shirā’, Islamic Economic Law.